(untitled) (Namibian Journal for Research, Science and Technology, 2020)
When employees are satisfied with their lives, the satisfaction spill over to their work life and help them to engage in helping behaviour. This study investigated the relationship between job satisfaction, organisation citizenship behaviour and satisfaction with life of employees in the Khomas Region. The sample consisted of n=151 secondary school teachers and n=150 NamPower employees. The questionnaire consisted of the Job Satisfaction Survey (JSS), the Organizational Citizenship Behaviour Checklist (OCB-C) and the Satisfaction with Life (SWL) scale. The findings revealed a negative relationship between job satisfaction and OCB-I (individual). A positive relationship was reported between job satisfaction and OCB-O (organisation). Job satisfaction reported a positive relationship with satisfaction with life. OCB-I and OCB-O reported positive relationships with satisfaction with life. This study recommends the need to focus on enhancing job satisfaction since it will increase satisfaction with life, OCB-I and OCB-O of employees. This can be done by implementing team building to strengthen relationships between supervisors and co-workers. Decision making, rewards, promotion and supervision should be fair and adequate. Possible interventions could focus on the increase of incentives, salaries or benefits, and recognition through employee of the month initiatives. It is further recommended that supervisors receive leadership training to enhance effective leadership at the workplace.